End User Computing Satisfaction (EUCS) Untuk Mengukur Tingkat Kepuasan Pengguna Aplikasi Mobile Assesment Minat Anak di Hompimpaa Alaium Gambreng - Fiby Nur Afiana; Zanuar Rifai; Hanun Karomatunnisa; Luzi Dwi Oktaviana; Ika Romadoni Yunita; Ranggi Praharaningtyas Aji; Toni Anwar (PROGRAM STUDI SISTEM INFORMASI INSTITUT SAINS DAN TEKNOLOGI NASIONAL (ISTN), 2022)
The initial idea of Hompimpaa.id is to provide access to early childhood education from home for every parent which is conceptualized according to the child's interests and tal-ents through Assessment. Assessment in hompimpaa is a technology that makes data as knowledge and the final result in the form of children's interests and talents. With the de-velopment of using Artificial Intelligence (AI) technology to process assessment features on mobile phones. These problems can be the background of the Mobile Assessment Ap-plication of children's interests and potentials. Therefore, a measurement of the level of satisfaction of the Mobile Assessment Application user's interest and potential will be car-ried out to determine the level of understanding of the existing menu structure. Factor analysis measuring user satisfaction level will be carried out on the variables of content, accuracy, format, ease of use and timeliness using the End User Computing Satisfaction (EUCS) method. Collecting data obtained from distributing questionnaires will then be distributed to 70 real users. Based on the results of the analysis, it can be seen that there are two groups of factors, namely factors that have a positive and significant effect con-sisting of content, format, and accuracy variables while the other two variables produce factors that do not have a positive and significant effect consisting of ease of use and time-liness.